Strengthening of National Identity Through Personality Development Based on Ethno- Pedagogy at Higher Education - Mukhibat, M (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to analyze the role of IAIN Ponorogo in reorient and optimize course family of“civic education”teaching and learning that concern with humanity values according to its culture; the virtue of education is not reduced into superficial things. Therefore, the terminology of education based on ethno-pedagogy becomes an appropriate and relevant term for understanding ethnic cultures that is rich with local wisdom values that reflect the identity of the ethnic group or nation. Ethno-pedagogy views local knowledge and local wisdom as “teaching as a cultural activity” and “the culture of teaching”. Ethno-pedagogy is also an effective way to cope with the embodiment of radicalism and terrorism. The contextualization of local cultural values in civic education can interpret local wisdom based on humanity so that the exclusive political piety can be reproduced into political piety based on social, cultural, and environmental.